2021
DOI: 10.1590/1678-4685-gmb-2020-0448
|View full text |Cite
|
Sign up to set email alerts
|

Genetic information improves the prediction of major adverse cardiovascular events in the GENEMACOR population

Abstract: The inclusion of a genetic risk score (GRS) can modify the risk prediction of coronary artery disease (CAD), providing an advantage over the use of traditional models. The predictive value of the genetic information on the recurrence of major adverse cardiovascular events (MACE) remains controversial. A total of 33 genetic variants previously associated with CAD were genotyped in 1587 CAD patients from the GENEMACOR study. Of these, 18 variants presented an hazard ratio >1, so they were selected to construct a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…According to a twin study, the heritability estimates of CAD mortality was found 0.57 in male and 0.38 in female, with genetic factors playing a role throughout the entire lifespan [11]. A wGRS incorporated into risk prediction models for CAD can enhance risk assessment in addition to the traditional models [12] and…”
mentioning
confidence: 99%
“…According to a twin study, the heritability estimates of CAD mortality was found 0.57 in male and 0.38 in female, with genetic factors playing a role throughout the entire lifespan [11]. A wGRS incorporated into risk prediction models for CAD can enhance risk assessment in addition to the traditional models [12] and…”
mentioning
confidence: 99%